Stability-indicating HPLC-DAD method for the determination of Granisetron hydrochloride in its pharmaceutical preparations - Mokhtar Mabrouk, Hamed El-Fatatry, Ismail Hewala and Ehab Emam (Journal of Applied Pharmaceutical Science, 2013)
A selective and reproducible high performance liquid chromatographic method has been developed for the determination of granisetron hydrochloride in presence of its hydrolytic, oxidation, photodecomposition and thermal degradation products. Successful separation of granisetron from its degradation products is achieved on X-Bridge C18 column using acetonitrile: 0.025 M KH2PO4 solution (20:80) adjusted to pH 2 as mobile phase. The method is selective for the determination of granisetron hydrochloride, benzyl alcohol (preservative) and sodium benzoate (preservative) in presence of benzaldehyde; the oxidation product of benzyl alcohol. The method is validated and validation acceptance criteria are met in all cases. Recovery experiments of granisetron hydrochloride, benzyl alcohol and sodium benzoate from a mixture of ICH stress-formed degradation products and benzaldehyde are between 99.5-100.5% with RSD% values less than 1.5%. The proposed validated stability-indicating method is applied to the determination of granisetron and the co-formulated preservatives in tablets, oral solution and injections.
Keywords: Granisetron, degradation, stability- indicating HPLC